1996
DOI: 10.1101/gr.6.3.187
|View full text |Cite
|
Sign up to set email alerts
|

The human CAS (cellular apoptosis susceptibility) gene mapping on chromosome 20q13 is amplified in BT474 breast cancer cells and part of aberrant chromosomes in breast and colon cancer cell lines.

Abstract: The CAS (cellular apoptosis susceptibility) gene is the human homolog of the yeast chromosome segregation gene CSE1. CAS may have a dual function in mammalian cells, one in apoptosis and another in cell proliferation. We have now mapped the CAS gene to chromosome 20q13. This region is known to harbor amplifications that correlate with aggressive breast cancer. Southern hybridizations with a CAS cDNA fragment and fluorescent in situ hybridization (FISH) with a P1 clone containing the CAS gene show elevated copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 14 publications
0
60
0
Order By: Relevance
“…The CROC1/UEV1-1 gene is located on chromosome 20q13.2 (Sancho et al, 1998), a region frequently ampli®ed in many types of human cancer . Others have reported that SW480 cells contain aberrant chromosomes harboring large portions of 20q (Brinkmann et al, 1996), a ®nding that may account, at least in part, for the high level of CIR1/CROC1 mRNA present in this cell line.…”
Section: Expression Of Cir1/croc1 In Human Tissues and Tumor-derived mentioning
confidence: 83%
“…The CROC1/UEV1-1 gene is located on chromosome 20q13.2 (Sancho et al, 1998), a region frequently ampli®ed in many types of human cancer . Others have reported that SW480 cells contain aberrant chromosomes harboring large portions of 20q (Brinkmann et al, 1996), a ®nding that may account, at least in part, for the high level of CIR1/CROC1 mRNA present in this cell line.…”
Section: Expression Of Cir1/croc1 In Human Tissues and Tumor-derived mentioning
confidence: 83%
“…A similar frequency (85%) of chromosome arm 20q gains in metastases was observed previously. 12 Four different genes, the cellular apoptosis susceptibility gene (CAS), 37 the steroid receptor coactivator gene (AIB1), 38 a putative serine/threonine kinase gene (BTAK/Aurora2) 39 -41 and DcR3, 42 were identified within this amplicon. In addition, a novel zinc finger gene mapped on 20q13.2 was amplified in human breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…40 However gains of 20q have been observed in solid tumors such as colorectal carcinoma, 41,42 breast, 43 bladder, 44 ovarian, 45 and pancreatic cancer. 46 Several candidate genes have been identified on 20q: the cellular apoptosis susceptibility (CAS) gene; 47 BTAK, a putative serine/threonine kinase gene; 48 AIB1, a steroid receptor co-activator gene; 49 PTPN1, a nonreceptor tyrosine phosphatase involved in growth regulation; 50 as well as MYB12, which encodes a transcription factor and plays an important role in cell cycle progression. 51 Regarding gene amplifications, CGH studies are detecting an increased number of high-level DNA amplifications in lymphomas, which were relatively rare in NHL by cytogenetic studies.…”
Section: Discussionmentioning
confidence: 99%